Phytochemical screening, in vitro antioxidant, photoprotective and hemolytic activities of ethyl acetate extracts of the fruits and branches from Spondias tuberosa (umbu) (Research, Society and Development, 2021)
Spondias tuberosa is a medicinal plant used to treat inflammatory conditions and digestive disorders. The phytochemical screening, antioxidant, photoprotective and hemoytic activities of ethyl acetate extracts from the fruits and branches were investigated. Antioxidant activities were evaluated using DPPH, ABTS and phosphomolybdenum assays. The photoprotective and hemolytic activities was evaluated by the spectrophotometric method. Identification of compounds classes from the ethyl acetate branches extract was performed by HPLC. TLC analysis demonstrated presence of flavonoids, cinnamic derivatives, triterpenes and steroids in both extracts, and proanthocyanidins and leucoanthocyanidins only in branches, and it was identified by HPLC gallic acid, chlorogenic acid, caffeic acid, ferulic acid in the ethyl acetate extract of branches. Ethyl acetate branches extracts showed the best results: total phenolic compounds (83.88 ± 0.2 mg GAE/g), flavonoids (11.24 ± 2.0 mg QE/g), DPPH (88.80 ± 0.4 %), ABTS (68.92 ± 0.7%), phosphomolybdenum (27.94 ± 0.26%) and sun protection factor (SPF) with 15.50 ± 0.41. In addition, both extracts did not present hemolytic activity. Therefore, the branches extracts can be used in the production of photoprotective application with phytocosmetics. This work is the first report of photoprotective activity of Spondias tuberosa (umbu).